A small-diameter vascular graft immobilized peptides for capturing endothelial colony-forming cells - Tang, Yaqi; Yin, Lu; Gao, Shuai; Long, Xiaojing; Du, Zhanhui; Zhou, Yingchao; Zhao, Shuiyan; Cao, Yue; Pan, Silin (Frontiers in Bioengineering and Biotechnology, 2023)
The combination of synthetic polymers and biomacromolecules could make up for the deficiency of thrombogenic and intimal hyperplasia in small-diameter vascular scaffolds (SDVGs). In the present study, an electrospinning poly(L)-lactic acid (PLLA) bilayered scaffold consisting of an outer layer scaffold for supporting and an inner biomimetic membrane combinate with heparin (Hep), peptide Arg-Glu-Asp-Val (REDV), and vascular endothelial growth factor (VEGF) has been developed to prevent thrombosis after implantation, promoting capture and differentiation of endothelial colony-forming cells (ECFCs). Attenuated Total Reflection Fourier Transform Infrared (ATR-FTIR), X-ray photoelectron spectroscopy (XPS), and contact angle goniometer were performed to identify its successful synthesis. The tensile strength of the outer layer was obtained based on the recorded stress/strain curves. Hemocompatibility was evaluated by the blood clotting test, platelet, and protein adhesion status. Captured ECFCs in vitro and measured proliferation, function, and differentiation on various surfaces. Scanning electronic microscopy (SEM) was used to observe the morphology of ECFCs on the surface.The outer layer of scaffolds exhibited a similar strain and stress performance as the human saphenous vein through tensile experiment. The contact angle decreased continuously until it reached 56° after REDV/VEGF modification. SEM image of platelet adhesion showed a better hemocompatibility surface after being modified. ECFCs were captured by the REDV+ VEGF+ surface successfully under sheer stress. The expression of mature ECs was constantly increased with the culture of ECFCs on REDV+ VEGF+ surfaces. SEM image showed that the ECFCs captured by the REDV+ VEGF+ surface formed capillary-like structures after 4 weeks of culture. The SDVGs modified by REDV combined with VEGF promoted ECFC capture and rapid differentiation into ECs which formed capillary-like structures in vitro. The bilayered SDVGs showed the potential to be used as a vascular device to achieve a high patency rate and rapid re-endothelialization.